MENINGKATKAN KINERJA KARYAWAN BAGIAN PRODUKSI MELALUI PROMOSI JABATAN PADA PT. SUNTORY GARUDA FOOD TBK CABANG PEKANBARU - Risman, Risman; Sasmita, Gusryana (Eko dan Bisnis: Riau Economic and Business Review, 2020)
This research was conducted at PT. Suntory Garuda Food Tbk, Pekanbaru branch, with the variable promotion research position (X) and employee performance (Y). Aimed to find out the effect of promotion in the performance of employees in the production department at PT. Suntory Garuda Food Tbk, Pekanbaru branch. This study uses a descriptive quantitative method, with a population and sample of 46 people, valid and reliable instrument testing. Results: the regression test result Y = 14,684 + 0,715X Constant (a) of 14,684 meant that when there was no promotion or zero, then the employee's performance was obtained at 14,684 units. While the influence of job promotion on employee performance is positive as evidenced from the results of the regression coefficient (b) of 0.715 which means that every promotion increase in one unit position will be able to increase employee performance by 0.715 units. The test is obtained t count of 7.690 and also based on the test table The significance obtained by t table is 2.021. From the two tests it was concluded that t arithmetic (7,690)> t table (2,021). And the results of the hypothesis test in this study is the promotion of position has a significant effect on employee performance. The R square obtained R-square value (coefficient of determination) of 0.573, and this means that the influence of job promotion variables on employee performance variables is 57.3% while the remaining 42.7% is influenced by other variables outside the promotion variable not discussed in this study